Konsep Media Dalam Tafsir Dakwah: Analisis Tafsir Surat Ibrahim Ayat 4 Dan Surat Al-An’am Ayat 75 - Fathya Azzahra’ (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2022)
This paper discusses the concept of media in Islamic da'wah. Da'wah activity is essentially a process of normative change in accordance with Islamic teachings, namely the Qur'an and the Sunnah of the Prophet Muhammad SAW. Da'wah is the responsibility of every Muslim regardless of his profession to be able to convey Islamic religious messages to the community. When the da'i conveys the message of da'wah, of course, it must have effective means, so that the purpose of da'wah can be understood by the mad'u community well. One of the important elements for the success of da'wah is the media of da'wah. The concept of media in da'wah has been stated in the Qur'an. The propaganda media verses in the Qur'an also always require review and reinterpretation to gain new insights. In this paper, the author uses a library research method or approach. The results of this study are the understanding of da'wah media, types of media in da'wah, and analysis of QS Ibrahim verse 4 and QS Al-An'am verse 75. Da'wah media can also develop following the current developments